2014
DOI: 10.1177/1040638714528502
|View full text |Cite
|
Sign up to set email alerts
|

Canine parvovirus 2c infection in a cat with severe clinical disease

Abstract: Abstract. Canine parvovirus 2 (CPV-2) is considered the main pathogen responsible for acute gastroenteritis in dogs, causing vomiting and hemorrhagic enteritis mainly. However, infection in cats by CPV variants causes clinical signs similar to Feline panleukopenia virus. The current study reports a case of CPV-2c in a domestic cat, in Portugal. The findings suggest that more surveys are needed to know the true prevalence and significance of cats in CPV epidemiology worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 22 publications
2
29
0
7
Order By: Relevance
“…Despite the widespread circulation of CPV in Australia, this virus was not detected in any samples tested in these FPL outbreaks. Canine parvovirus causes approximately 5% of FPL cases globally, but these have been confined to sporadic individual cases, and there are no reports of FPL outbreaks caused by CPV in multi-cat environments [8,15,16]. Whether this is due to viral or to host factors is currently unknown and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread circulation of CPV in Australia, this virus was not detected in any samples tested in these FPL outbreaks. Canine parvovirus causes approximately 5% of FPL cases globally, but these have been confined to sporadic individual cases, and there are no reports of FPL outbreaks caused by CPV in multi-cat environments [8,15,16]. Whether this is due to viral or to host factors is currently unknown and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CPV-2a and -2b viruses have been also isolated in feline cells in vitro and in domestic cats in vivo from Japan, USA, Taiwan and Vietnam (Truyen et al, 1995(Truyen et al, , 1996aMochizuki et al, 1996;Ikeda et al, 2000). Diseased cats have also been detected with CPV-2c (Miranda et al, 2014) or co-infections by multiple CPV variants (Battilani et al, 2006) or mixed infections with FPV and CVP-2-like (Url et al, 2003;Battilani et al, 2011). Some studies have also reported the presence of CPV-2 variants in faecal and bone marrow samples of healthy cats (Clegg et al, 2012;Haynes & Holloway, 2012).…”
Section: Host Ranges For Antigenic Cpv-2 Variants Domestic Catsmentioning
confidence: 99%
“…This variant was subsequently shown to affect adult and immunized dogs, and also cats (Buonavoglia et al 2001, Decaro & Buonavoglia 2012, Miranda et al 2014, quickly spread out and became established in dog populations throughout the world (Cotmore & Tattersall 1996, Buonavoglia et al 2001, Pérez et al 2007, Streck et al 2009, Nandi & Kumar 2010, Parthiban et al 2010. Up to the present, the CPV-2c variant has been detected in high frequencies in many countries.…”
Section: Introductionmentioning
confidence: 99%